A New Textbook Design in Language Teaching: Plurimethodological Pair-unit - Acar, Ahmet (JET (Journal of English Teaching), 2024)
In this paper, I propose a model of plurimethodological approach in ELT textbook design, in which one unit is based on the communicative PPP unit model, where the unit ends with a final communicative task, and the following unit is based on the action-oriented unit model, where the unit is a mini-project unit as a whole. Such a textbook model is based on the concept of plurimethodological pair-unit, where the communicative approach and the action-oriented approach are combined in coherence and synergy. In such a plurimethodological textbook design, the topics of the two successive units (one PPP unit and the other mini-project unit) are the same or closely related, so that the unit based on the PPP model will provide the students with much of the language and documentary resources needed to complete the mini-project in the following unit. The mini-project unit will provide the students with additional language and documentary resources for carrying out the mini-project, but as there will be less language and documentary work for students in this unit, students will be better able to concentrate on carrying out the mini-project.